Effects of Storage Temperature and Time on Stability of Serum Tacrolimus and Cyclosporine A Levels in Whole Blood by LC-MS/MS - İbrahim Kaplan; Hatice Yüksel; Osman Evliyaoğlu; M. Kemal Basarali; Gülten Toprak; Leyla Çolpan; Velat Şen (International Journal of Analytical Chemistry)
Tacrolimus and cyclosporine A are immunosuppressant drugs with narrow therapeutic windows. The aim of this study was to investigate the stability of tacrolimus and cyclosporin A levels in whole blood samples under different storage conditions. Whole blood samples were obtained from 15 patients receiving tacrolimus and 15 patients receiving cyclosporine A. Samples were immediately analyzed and then stored at different conditions (room temperature (24°C−26°C) for 24 hours, +4°C for 24 and 48 hours, and −20°C for one month) and then analyzed again. For tacrolimus, there was a significant difference between samples analyzed immediately and those kept 24 hours at room temperature (P=0.005) (percent change 32.89%). However, there were no significant differences between the other groups. For cyclosporine A, there was a significant difference between samples analyzed immediately and those kept 24 hours (P=0.003) (percent change 19.47%) and 48 hours (P=0.002) (percent change 15.38%) at +4°C and those kept 24 hours at room temperature (P=0.011) (percent change 9.71%). Samples of tacrolimus should be analyzed immediately or stored at either +4°C or −20°C, while samples of cyclosporine A should be analyzed immediately or stored at −20°C.